Acute Vertical Pendular Nystagmus and Delayed Oculopalatal Tremor in a Patient with Bilateral Horizontal Gaze Palsy - Lee, Hyung; Kim, Hyun Ah (Journal of clinical neurology (Seoul, Korea), 2020)
KCI Citation Count: 0